Persepsi Mahasiswa Tentang Keterampilan Mengajar Dosen Dan Pola Belajar Terhadap Keaktifan Mahasiswa Dalam Proses Pembelajaran Sistem Akuntansi Pada Mahasiswa Program Studi Pendidikan Akuntansi FKIP UMS Angkatan 2013 - , Widowati; , Dr.Suyatmini,SE.,M.Si (2016)
The purpose of this study to determine: 1) influence the perception of students about the teaching skills of lecturers to the liveliness of the students in the learning process of accounting systems in student Accounting Education FKIP UMS force in 2013, 2) influence learning patterns of the activeness of students in the learning process of accounting systems in student Accounting Education FKIP UMS force in 2013, and 3) influence students' perceptions of faculty teaching skills and learning patterns of the activity of students in the learning process in the accounting system accounting Education students of UMS FKIP force in 2013 . This study uses quantitative methods associative. The population in this study were students of Accounting Education who took a course in Accounting Systems class of 2013 is 114 students. The sampling technique using Proportional Random Sampling as many as 84 respondents. The necessary data and documentation obtained through a questionnaire that has previously been tested by validity and reliability testing. Data analysis technique used is multiple linear regression, F test, t-test, R2, and the relative contribution and effective. Results of regression analysis regression equation: Y = 7,252+ 0,138X1 + 0,277X2. The conclusion of this study were: 1) Perception of students on faculty teaching skills significantly influence the activity of students in the learning process in the accounting system Accounting Education students of UMS force FKIP 2013. Based on t test obtained t> t table is 3.948> 1.990 (α = 5%) and the significance value <0.05 is 0.002. 2) The pattern learning significant effect on the activity of the student in the learning process in the accounting system Accounting Education students FKIP UMS force in 2013.Based on t test obtained t> t table is 5,000> 1,990 (α = 5%) and the significance value <0.05 is 0.000. 3) student perceptions of faculty teaching skills and learning patterns significantly influence the activity of students in the learning process in the accounting system Accounting Education students FKIP UMS force F 2013. Based on test results obtained Fhitung> Ftable is 42.253> 3.109 at a significance level of 5%. 4) Variable X1 gives the relative contribution of 42.3% and the effective contribution of 21.62%, X2 gives the relative contribution of 57.7% and the effective contribution of 29.52%. 5) The calculation result R2 obtained 0.511, meaning 51.1% of students in the learning process liveliness accounting system is influenced by students' perceptions of faculty teaching skills and learning patterns, the remaining 48.9% influenced by variables outside the research.